Lattice rings: an interpretation of L-fuzzy rings as habitual algebraic structures - Kurdachenko, L.A.; Ya, I.; Yashchuk, V.S. (Algebra and Discrete Mathematics, 2017)
In this paper, we introduce some algebraic structure associated with rings and lattices. It appeared as the result of our new approach to the fuzzy rings and L-fuzzy rings where L is a lattice. This approach allows us to employ more convenient language of algebraic structures instead of currently accepted language of functions.